Digital Transformation of Public Administration in Higher Education Environment: A Case Study of Lombok Business Academy - Stiaman, Stiaman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine how the digital transformation process in public administration is implemented in a higher education environment, specifically at the Lombok Business Academy. The approach used in this study is a descriptive qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The results of the study indicate that the Lombok Business Academy has implemented a digital-based administration system through the use of the Academic Information System (SIKAD) and the Learning Management System (LMS). SIKAD makes it easier for students to access academic services such as filling out KRS and checking KHS, while the LMS is used to support the online learning process. This digital transformation has a positive impact on the efficiency, transparency, and quality of campus administrative services. However, several challenges, such as limited infrastructure, unequal digital literacy, and suboptimal system utilization, still require attention. This study illustrates that digital transformation in the higher education environment is an important step in realizing modern and adaptive educational governance.